Nation, society and culture in North Africa - McDougall, James, 1974- (Cass series--history and society in the Islamic world, 2003)
The essays in this volume explore the complexities of the relationship between states, social groups and individuals in contemporary North Africa, as expressed through the politics, culture and history of nationhood.